Combination of Atrial Fibrillation and Coronary Heart Disease in Patients in Clinical Practice: Comorbidities, Pharmacotherapy and Outcomes (Data from the REСVASA Registries) - M. M. Loukianov; S. Yu. Martsevich; E. Yu. Andrenko; S. S. Yakushin; A. N. Vorobiev; K. G. Pereverzeva; A. V. Zagrebelny; Е. Yu. Okshina; V. V. Yakusevich; Vl. Vl. Yakusevich; E. M. Pozdnyakova; T. A. Gomova; et al. (Рациональная фармакотерапия в кардиологии, 2021)
Aim. Assess the structure of comorbid conditions, cardiovascular pharmacotherapy and outcomes in patients with atrial fibrillation (AF) and concomitant coronary artery disease (CAD) included in the outpatient and hospital RECVASA registries.Materials and methods. 3169 patients with AF were enrolled in outpatient RECVASA (Ryazan), RECVASA AF-Yaroslavl registries and hospital RECVASA AF (Moscow, Kursk, Tula). 2497 (78.8%) registries of patients with AF had CAD and 703 (28.2%) of them had a previous myocardial infarction (MI).Results. There were 2,497 patients with a combination of AF and CAD (age was 72.2±9.9 years; 43.1% of men; CHA2DS2-VASc – 4.57±1.61 points; HAS-BLED – 1.60±0,75 points), and the group with AF without CAD included 672 patients (age was 66.0±12.3 years; 43.2% of men; CHA2DS2-VASc – 3.26±1.67 points; HAS-BLED – 1,11±0.74 points). Patients with CAD were on average 6.2 years older and had a higher risk of thromboembolic and hemorrhagic complications (p<0.05). 703 patients with a combination of AF and CAD had the previous myocardial infarction (MI; age was 72.3±9.5 years; 55.2% of men; CHA2DS2-VASc – 4.57±1.61; HAS-BLED – 1.65±0.76), and 1794 patients didn't have previous MI (age was 72.2±10.0 years; 38.4% of men; CHA2DS2-VASc – 4.30±1.50; HAS-BLED – 1.58±0.78). The proportion of men was 1.4 times higher among those with the previous MI. Patients with a combination of AF and CAD significantly more often (p <0.0001) than in the absence of CAD received a diagnosis of hypertension (93.8% and 78.6%), chronic heart failure (90.1% and 51.2%), diabetes mellitus (21.4% and 13.8%), chronic kidney disease (24.8% and 17.7%), as well as anemia (7.0% and 3.0%; p=0.001). Patients with and without the previous MI had the only significant difference in the form of a diabetes mellitus higher incidence having the previous MI (27% versus 19.2%, p=0.0008). The frequency of proper cardiovascular pharmacotherapy was insufficient, mainly in the presence of CAD (67.8%) than in its absence (74.5%), especially the prescription of anticoagulants (39.1% and 66.2%; p <0.0001), as well as in the presence of the previous MI (63.3%) than in its absence (74.3%). The presence of CAD and, in particular, the previous MI, was significantly associated with a higher risk of death (risk ratio [RR]=1.58; 95% confidence interval [CI] was 1.33-1.88; p <0.001 and RR=1.59; 95% CI was 1.33-1.90; p <0.001), as well as with a higher risk of developing a combined cardiovascular endpoint (RR=1.88; 95% CI was 1.17-3 , 00; p <0.001 and RR=1.75; 95% CI was 1.44-2.12; p<0.001, respectively).Conclusion. 78.8% of patients from AF registries in 5 regions of Russia were diagnosed with CAD, of which 28.2% had previously suffered myocardial infarction. Patients with a combination of AF and CAD more often than in the absence of CAD had hypertension, chronic heart failure, diabetes, chronic kidney disease and anemia. Patients with the previous MI had higher incidence of diabetes than those without the previous MI. The frequency of proper cardiovascular pharmacotherapy was insufficient, and to a greater extent in the presence of CAD and the previous MI than in their absence. All-cause mortality was recorded in patients with a combination of AF and CAD more often than in the absence of CAD. All-cause mortality and the incidence of nonfatal myocardial infarction were higher in patients with AF and the previous MI than in those without the previous MI. The presence of CAD and, in particular, the previous MI, was significantly associated with a higher risk of death, as well as a higher risk of developing a combined cardiovascular endpoint.